(untitled) (Academia Science Repository, 2023)
This article discusses the theoretical aspects of the concept of inflation and inflation targeting at the present stage of economic development and analyzes the role of inflationary expectations in the monetary mechanism of the Republic of Uzbekistan, provides the main statements and recommendations of foreign international experts. It also presents a description of the role and importance of inflation expectations and inflation targeting in the fight against inflation.